2017
DOI: 10.1093/mnrasl/slx012
|View full text |Cite
|
Sign up to set email alerts
|

New quantum chemical computations of formamide deuteration support gas-phase formation of this prebiotic molecule

Abstract: Based on recent work, formamide might be a potentially very important molecule in the emergence of terrestrial life. Although detected in the interstellar medium for decades, its formation route is still debated, whether in the gas phase or on the dust grain surfaces. Molecular deuteration has proven to be, in other cases, an efficient way to identify how a molecule is synthesised. For formamide, new published observations towards the IRAS16293-2422 B hot corino show that its three deuterated forms have all th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 37 publications
6
78
0
Order By: Relevance
“…For example, high spatial resolution observations of formamide line emission towards the protostellar shock site L1157-B1 have demonstrated that the formation of formamide is dominated by the gas-phase reaction NH 2 + H 2 CO 65 , a reaction theoretically studied by some of us. 66,67 On the same line, observations of the deuterated forms of formamide (namely containing D rather than H atoms) also provide strong constraints on the formation route of this species in the hot corino of the solar-type protostar IRAS 16293-2422.…”
Section: Astrophysical Implicationsmentioning
confidence: 92%
“…For example, high spatial resolution observations of formamide line emission towards the protostellar shock site L1157-B1 have demonstrated that the formation of formamide is dominated by the gas-phase reaction NH 2 + H 2 CO 65 , a reaction theoretically studied by some of us. 66,67 On the same line, observations of the deuterated forms of formamide (namely containing D rather than H atoms) also provide strong constraints on the formation route of this species in the hot corino of the solar-type protostar IRAS 16293-2422.…”
Section: Astrophysical Implicationsmentioning
confidence: 92%
“…Gas-phase synthesis of formamide via the NH 2 + H 2 CO → NH 2 CHO + H reaction has recently gained support by quantum chemical and kinetic calculations. [27][28][29] Comparison of model predictions with astronomical observations showed that the proposed reaction can well reproduce the abundances of NH 2 CHO in the cold envelope of the Sun-like protostar IRAS16293-2422 and the molecular shock L1157-B1, two very different interstellar objects 20 . More recent dedicated observations of the formamide spatial distribution towards the molecular shock L1157-B1 provided additional support to its formation from the NH 2 + H 2 CO gas-phase reaction.…”
Section: K 26mentioning
confidence: 99%
“…Later, in the hot corino stage, gasphase molecules emit from much warmer and denser regions, where most ice will have sublimated into the gas phase. Gas-phase compositions therefore reflect thermal ice desorption and possibly additional gas-phase chemistry (Herbst & van Dishoeck 2009;Balucani et al 2015;Skouteris et al 2017Skouteris et al , 2019. Finally, we can best explore COM chemistry at the Class II disk stage using cometary measurements, which are made in the gasphase but are believed to probe pristine ices.…”
Section: Organic Abundances Across Evolutionary Stagesmentioning
confidence: 99%